Pedagogical Conditions for the Formation of Cognitive Activity in General Educational Processes in the Field of Physical Culture - Khudoyberdiyev Bakhtiyar Rakhmatillayevich (Genius Publishing Group, 2022)
This article presents an analysis of the pedagogical conditions for the formation of cognitive activity in general educational processes in the field of Physical Culture. In addition, the processes of formation of cognitive activity and the important stages of the theory process of formation of cognitive activity, as well as the humanistic principle, the principle of conscious and activity, the unity of consciousness and activity, the principle of substantiation, the principle of problemvicity, the principle of individualization, theory and practice are presented
Keywords: Physical Culture; general education; cognitive activity; the principle of humanism